MANAJEMEN PROGRAM INTENSIF BAHASA ARAB PADA PEMINATAN KEAGAMAAN MAN 2 KOTA MALANG - M. Rozy Zamroni; A'yunin Aditya Fajrin; Tabassum Aliyatuz Zahroh; Nur Kholid (Universitas Islam Negeri Alauddin Makassar, 2023)
The purpose of this research is to determine the planning and actuating of management in the intensive Arabic program for religion specialization as the MAN-PK stub of MAN 2 Kota Malang and to analyze the supporting factors and obstacles found in the process while running the program. The method used in this research is a qualitative method. The data obtained by observation and interviews were then analyzed descriptively. The results of this study are; (1) planning management program is carried out properly in accordance with the objectives of the program; (2) supporting teachers used strategies that accordance with planning and objectives in implementing the program; (3) the majority of students have the same orientation even though some students think to change their specialization is one of the obstacles in this intensive Arabic language program.